Ten Benefits of Urban Gardens: Focus on Socio-Economic Crises: FOR406/FR477, 9/2024 - Clarke, Mysha (EDIS, 2024)
Over 90 percent of Floridians live in urban areas. Many city dwellers are disconnected from or have limited exposure to the natural world. Urban green spaces, among them urban gardens, can provide various benefits to people and wildlife. These urban gardens provide important avenues for people to maintain their mental and physical health, reduce stress, and improve their general well-being. The COVID-19 pandemic highlighted the importance of urban green spaces. Community efforts to grapple with the evolving pandemic present an opportunity to reconsider the benefits of urban gardens This publication is intended to assist Extension agents, gardeners, garden managers, and urban planners interested in adding new gardens and supporting and promoting existing gardens in Florida’s urban communities. To that end, it lists and explains 10 major benefits urban gardens provide to ecosystems and people.